Risk factors for synchronous high-risk polyps in patients with colorectal cancer - He, Degao; Chen, Junguo; Jiang, Xuefei; Chen, Hao; Huang, Juanni; Chen, Zexian (Frontiers in Surgery, 2024)
Purpose: Colorectal cancer (CRC) patients may experience inadequate preoperative colonoscopy due to bowel obstruction or inadequate bowel preparation, leading to potential oversight of other polyps. We aimed to identify risk factors for CRC complicated with synchronous high-risk polyps.Methods: A retrospective analysis of 6,674 CRC patients from December 2014 to September 2018 was conducted. High-risk polyps were defined as adenomas or serrated polyps that were ≥10 mm, or with tubulovillous/villous components or high-grade dysplasia. All other polyps were defined as low-risk polyps. Patients with complete pathological and clinical information were categorized into three groups: the no polyp group, the low-risk polyp group, and the high-risk polyp group. Univariate and multivariate logistic regression analyses were performed to calculate the odds ratios (ORs) and corresponding 95% confidence intervals (CIs) for all potential risk factors.Results: Among the 4,659 eligible patients, 848 (18.2%) were found to have low-risk polyps, while 675 (14.5%) were diagnosed with high-risk polyps. In a multivariate logistic regression model, compared to patients without polyps, those with synchronous high-risk polyps were more likely to be male (OR= 2.07), aged 50 or older (OR= 2.77), have early-stage tumors (OR= 1.46), colon tumors (OR= 1.53), NRAS mutant tumors (OR= 1.66), and BRAF wild-type tumors (OR= 2.43).Our study has identified several risk factors associated with the presence of synchronous high-risk polyps in CRC patients. Based on these findings, we recommend that patients who exhibit these high-risk factors undergo early follow-up of colonoscopy to detect synchronous polyps early.